Ischemic Preconditioning Alleviates Mouse Renal Ischemia/Reperfusion Injury by Enhancing Autophagy Activity of Proximal Tubular Cells - Shun Zhang; Weimin Xia; Huangqi Duan; Xinyan Li; Subo Qian; Haibo Shen (Karger Publishers, 2022)
Objectives: Ischemia/reperfusion injury (IRI) is one of the most vital pathogenesis leading to kidney injury but lacks effective prevention and treatment strategies. This study was conducted to investigate the influences of ischemic preconditioning (IPC) on the pathological process of mouse renal IRI (RIRI) and to figure out the role of autophagy of proximal tubular cells (PTCs) in this process. Methods: C57BL/6J mice were randomized to three groups, i.e., sham-operated group, ischemia/reperfusion (I/R) group, and IPC + I/R group. Meanwhile, 3-methyladenine, an autophagy inhibitor, was administered when further verification was needed. Histological and functional severity of kidney injury, the autophagy and apoptosis activity of PTCs, as well as the characterization of the immune cell infiltration landscape in kidney tissues were investigated. Furthermore, HK-2 cells and primary cultured PTC were cultured to set up the hypoxic preconditioning and hypoxia/reoxygenation model for in vitro simulation and verification, and a microarray dataset derived from the Gene Expression Omnibus database was analyzed to explore the transcriptome profiles after IPC. Results: IPC could significantly attenuate I/R-induced kidney injury functionally and histologically both in the acute and recovery phase of RIRI by enhancing the autophagy activity of PTCs. Cell autophagy could regulate the release of monocyte chemoattractant protein-1, and sequentially decrease macrophages infiltration in kidney tissues in the acute phase of RIRI, thus mediating the reno-protective effect. Conclusions: IPC could attenuate mouse RIRI-induced kidney injury. IPC-mediated activation of autophagy of PTCs plays a vital role in affording protection in RIRI-induced kidney injury.